Implementation of Rational Emotive Behavior Therapy in Overcoming Deviant Sexual Orientation: A Case Study - Safitri, Bella; Noviza, Neni; Dewi, Emi Puspita (Scidacplus, 2024)
Deviant sexual orientation, particularly same-sex attraction, is a complex issue that often results from various internal and external factors. This research formulates several key issues: what is the form of deviant sexual orientation in the subject, what factors cause this deviant sexual orientation, and how can Rational Emotive Behavior Therapy (REBT) be applied to address it? This study uses a qualitative approach with a case study method, focusing on a subject, referred to as